The nature of censorship and regulation of the darknet in the Digital Age - Peteva, Petya (Wydawnictwo C.H. Beck, 2020)
Latest data from Freedom House shows that, up to date, over 3.8 billion people have access to the Internet. With the advance of the Information Age and with the ever-growing number of Internet users worldwide, multiple heated debates continue taking place on whether cyberspace should be regulated and/or censored, and to what extent, so that it strikes the right balance between respecting fundamental human rights, such as freedom of expression on the one hand, and ensuring public security and safety on the other. While cyberspace censorship has turned to be a political hot potato, there are still corners of cyberspace that, in the meantime, are practically unregulatable due to their anonymity and intractability of their users. This so-called „darknet”, while not without its benefits, has also infamously posed a considerable obstacle for law enforcement authorities in combating crime and has provided a safe haven for nefarious individuals and illegal activities to take place with impunity.
Keywords: darknet; censorship; Internet regulation